Tupi or Not Tupi – That is the Question: On Semio-cannibalism, Its Variants, and Their Logics (Das Questões, 2021)
In this paper I argue that, if put into due anthropological perspective, Oswald de Andrade’s aphorism: “Tupi or not Tupi, that is the question,” does not exactly reverse the mainstream distribution of the terms involved in the colonial imaginary divide, but that it replaces the latter with an unthinkable (for the modern cogito) alter-oriented counter-logic, as “Tu-pi,” i.e. to be a Tupi, requires the intervention of a possible Other. Furthermore, I examine these two logics as semio-cannibal variants and analyse their differing conceptual matrixes against the backdrop of structural anthropology, in dialogue with Viveiros de Castro’s studies on cannibalism, kinship, and embodiment. I conclude that, paradoxically, whereas in one case the Other is fully erased albeit being metaphorically eaten, in the other case, despite the Other being physically eaten, its position is exchanged but never suppressed. Additionally, I attempt at a characterisation of capitalism as a form of semio-cannibalism and venture a new definition of ritual exo- cannibalism, on whose social function I offer a number of insights, as well.